Qualitative Exploration Study of Perceptions of Women and Nurse-Midwives on Antenatal Care Information and Communication in Tanzania - Heri R; Mselle LT; Malqvist M (Dove Medical Press, 2023)
Rashidi Heri,1 Lilian Teddy Mselle,2 Mats Malqvist3 1Department of Nursing Management, Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 2Department of Clinical Nursing, Muhimbili University of Health and Allied Sciences, Dar es Salaam, Tanzania; 3Department of Women's and Children's Health, Uppsala University, Uppsala, SwedenCorrespondence: Rashidi Heri, Email rashidiheri@gmail.comBackground: Antenatal health information enables pregnant women to make informed choices for their health during pregnancy and childbirth. Worldwide, evidence shows inadequate coverage of the information provided to women during antenatal care visits. Interaction between women and providers is important to ensure effective information exchange. This study aimed to explore women's and nurse midwives' perceptions of their interactions and the information they shared about care during pregnancy and childbirth in Tanzania.Methods: Formative explorative research using in-depth interviews was conducted with eleven Kiswahili-speaking women who had normal pregnancies and had more than three antenatal contacts. Also, five nurse-midwives who worked in the ANC clinic for a year or more were included in the study. A thematic analysis based on descriptive phenomenology guided the analysis of data that was informed by the WHO quality of care framework.Results: Two major themes emerged from the data, enhancing communication and respectful delivery of ANC information and receiving information about pregnancy care and safe childbirth. We found that women felt free to communicate and interact with midwives. Some women feared interacting with midwives and other midwives were difficult to approach. All women acknowledge receiving antenatal care information. However, not all women reported receiving all ANC information as per national and international guidelines. Inadequate staffing and time were the reasons for poor prenatal care information delivery.Conclusion: Women did not report most of the information provided during ANC contacts as per the national ANC guidelines. The inadequate number of nurse-midwives, increased number of clients, and insufficient time were reported to contribute to inadequate provision of information during antenatal care. Strategies for effective provision of information during antenatal contacts should be considered including using group antenatal care and information communication technology. Further, nurse-midwives should be sufficiently deployed and motivated.Keywords: antenatal care, health information, pregnant women, maternal and infant mortality, Tanzania